Deselection processes in selected academic libraries in Metro Manila - Dela Cruz, Leonida A.; Vallejo, Rosa M.; Arellano, Clarita A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1993)
This study explores the present state of deselection process or weeding in selected academic libraries in Metro Manila. It seeks to find out the nature and extent of weeding, the existence of deselection policies, if any, the deselection methods and criteria used, the methods of disposing the discarded stock and the problems encountered by the academic librarians in implementing the weeding process.
Eighteen academic libraries were surveyed and these are the Adamson University Library (AU), the Ateneo de Manila University (ADMU) Rizal Library; the College of Holy Spirit (CHS) Library, De La Salle University (DLSU) Library; Far Eastern University (FEU) Library; Jose Rizal College (JRC) Library; Lyceum of the Philippines - Sotero H. Laurel Library; Manila Central University (MCU) Main Library; Manuel L. Queszon University (MLQU) Library; Miriam College (MIRIAM) Library; Pamantasan ng Lungsod ng Maynila (PLM) - Celso Al Carunungan Memorial Library; Philippine Christian University (PCU) Library; Philippine Normal University (PNU) Library; Philippine Women's University (PWU) - Ramona S. Tirona Memorial Library, San Beda College (SBC) Library; University of Santo Tomas (UST) Central Library; University of the East (UE) Main Library; and University of the Philippines Diliman (UPD) Main Library.
The study used the descriptive survey method of research. A structured questionnaire was used as a tool in data collection. It was also designed to determine the nature and extent of the deselection process in each academic library surveyed.
Findings of this study showed that: 1) all academic libraries surveyed practice weeding or deselection of library materials, but only seven out of eighteen academic libraries follow a periodic weeding program; 2) twelve libraries have written weeding policies, to guide the staff in weeding the collection. One has an unwritten policy while another reported they are in the process of formulating a weeding policy. Four academic librarians perform weeding, but have no written guideline for deselection; 3) the principal methods used in weeding are shelf-time period and shelf-scanning/stock revision; 4) the criteria used for weeding the book collections are: removal of unwanted/unused volumes; duplicate volumes, physically worn out materials, weeding based upon age and weeding based upon use patterns. Other criteria used are: when micrifilm/microfiche copies become available; relevance to curriculum; and superseded issues/volumes. The two primary criteria for weeding the periodical collection are the periodicals with duplicate copies and serials of the news magazine type; 5) the methods of disposing the discarded stock are: given/donated to other libraries, distributed to interested students; just stored in stock room and thrown away as trash; and 6) deselection process is not a continuous or year-round activity in most of the academic libraries because of the following problems: a) lack of staff; b) lack of time; c) difficulty in getting faculty participation, etc.
Conclusions drawn from the study includes: 1) Since all academic libraries surveyed perform deselection process, it is an indication that they perceive the process as an important component of the collection development program; 2) academic librarians perform weeding, but most of them have no continuous or periodic weeding programs; and 3) weeding policies are used by most academic librarians in the deselection process, but there are still few who do not have written guidelines.
Based on the study's findings and conclusions, the author offers the following recommendations: 1) the implementation of a continuous and regular weeding process of at least once in every two years; 2) emphasize weeding of less-used materials by transferring/relocating them in a stock room rather totally discard them in as much as all are related to the curriculum; 3) for academic libraries with no weeding policies yet, formulate sound guidelines and perform deselection process in the light of these policies; and 4) to solve the deselection problems encountered by academic librarians, there should be lectures/seminars about weeding so that academic librarians would be made more aware of the importance of the process. Library associations specially PAARL should formulate local standards and/or criteria for deselecting library materials. Academic librarians should encourage faculty representatives to participate actively in the deselection process. Librarians should formulate guidelines/policies in accepting gifts and donations over and above the aforementioned recommendations.
Thesis (M.L.S.)--University of the Philippines, Diliman
Typescript
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Discarding of books, periodicals, etc; Libraries, University and college--Philippines--Manila Metropolitan Area; Weeding (Books) See Discarding of books, periodicals, etc